The interplay between TGF-β/SMAD and BMP/SMAD signaling pathways in the epithelial mesenchymal transition of A549 cells induced by silica. (4th May 2018) - Yu, Yanhua; Lin, Yanming; Yang, Gengxia; Tian, Lin
Abstract: The epithelial–mesenchymal transition (EMT) is a phenotype transdifferentiation of epithelial into mesenchymal cells and contributes to pulmonary fibrotic disease. SMAD-dependent pathway has been reported to play a key role in the multiple fibrotic diseases. We hypothesized that TGF-β/SMAD signaling could cross-interact with BMP/SMAD signaling pathways in silica-induced EMT in A549 cells. We investigated that the ability of silica-induced EMT in A549 cells, and this process was significantly inhibited by SB431542 through up-regulation of Vimentin, α-SMA and collagen type I expression and down-regulation of E-cadherin expression. Whereas BMP/SMAD inhibition using LDN193189 enhanced EMT. In addition, we also demonstrated that SB431542 could enhance BMP/SMAD signaling pathways in silica-induced EMT and vice versa. Therefore, our study provides evidence that the TGF-β/SMAD pathway was a crucial regulator in silica-induced EMT and that SB431542 could prevent the EMT. More importantly, we have identified that the interplay of TGF-β/SMAD and BMP/SMAD pathways in silica-induced EMT in A549 cells.